ARISTOTELIAN FRIENDSHIP SEEN IN STEPHEN KING'S THE BODY - Fitriya Muanah; Mateus Rudi Supsiadji (Anaphora : Journal of Language, Literary, and Cultural Studies, 2018)
This article explores tl1e aristotelia n friendship in King 's The Body to answer two questions: 1) how is friendship described in Stephen King 's The body?; 2) what kinds of friendships are  desscribed in Stephen King s The body? Aristotle grouped friendship into tlueefriendship based on utility ,friendship based on pleasure, andfoendship based on goodness. The  research method  applied  was qualitative descriptive.The result of the analysis showed  Gordie, Chris, Teddy and Vern performed friendship based  on  utility  and  lfriendship  based  on pleasure while Gordie and Chris perfonned in the friendship based on goodness because  only  both of them who always stayed to gethe r and shared goodness in their relationship , the y encouraged one another in good things. Chris showed his love and care to Gordie by the way he pushed Gordie to join the collage course and leave the gang because tlle gang will only drag him down.